2017
DOI: 10.1074/mcp.ra117.000065
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin-mediated Dephosphorylation of Acetyl-coA Carboxylase is Required for Pheromone Biosynthesis Activating Neuropeptide (PBAN)-induced Sex Pheromone Biosynthesis in Helicoverpa armigera

Abstract: Chemical signaling plays a critical role in the behavior and physiology of many animals. Female insects, as many other animals, release sex pheromones to attract males for mating. The evolutionary and ecological success of insects therefore hinges on their ability to precisely mediate (including initiation and termination) pheromone biosynthesis. Pheromone biosynthesis activating neuropeptide (PBAN) acts directly on pheromone glands to regulate sex pheromone production using Ca and cyclic-AMP as secondary mess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 54 publications
1
62
0
Order By: Relevance
“…The color presented on the insect body surface is regulated by multiple products in the pigment synthesis regulation network, which is reflected by the diverse phenotypes in response to melanin-related gene knockdown in BPH. Recently, pheromone biosynthesis activating neuropeptide has been found to directly activate acetyl-coA carboxylase, a key component in pheromone biosynthesis activating neuropeptideinduced sex pheromone biosynthesis via Ca 2+ / calcineurin-mediated dephosphorylation and cAMP/ PKA/AMPK-induced phosphorylation (38). Therefore, further efforts are required to examine whether or not elevenin signaling directly affects the activity of enzymes involved in the melanization pathway via phosphorylation and dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The color presented on the insect body surface is regulated by multiple products in the pigment synthesis regulation network, which is reflected by the diverse phenotypes in response to melanin-related gene knockdown in BPH. Recently, pheromone biosynthesis activating neuropeptide has been found to directly activate acetyl-coA carboxylase, a key component in pheromone biosynthesis activating neuropeptideinduced sex pheromone biosynthesis via Ca 2+ / calcineurin-mediated dephosphorylation and cAMP/ PKA/AMPK-induced phosphorylation (38). Therefore, further efforts are required to examine whether or not elevenin signaling directly affects the activity of enzymes involved in the melanization pathway via phosphorylation and dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Further Blast search and subsequent phylogenetic analyses demonstrated that this gene indeed encodes SREBP‐1c. The time expression profiles demonstrated that the fluctuation of the HaSEBP‐1c mRNA level is similar with that of other genes involved in sex pheromone biosyntheses, such as PBAN receptor, fatty acid reductase, desaturase, and ACC in H. armigera (Du et al, ). The expression pattern of HaSREBP‐1c is also similar to the changes of sex pheromone component titre, indicating that this gene possibly has associated with sex pheromone biosynthesis.…”
Section: Discussionmentioning
confidence: 90%
“…The nucleotide sequence of HaSREBP‐1c was first obtained from PG transcriptome data of H. armigera (Du et al, ) and further verified by PCR. Sequence analysis demonstrated that the open reading frame of HaSREBP‐1c consists of 3201 bp nucleotides that encode 1066 amino acid residues (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our present work also demonstrated that both the inhibitors and RNAi‐mediated knockdown of HaCNA caused a significant decrease in the male sex pheromone components in H. armigera male moths, consistent with the results in the female PGs of B. mori . Our previous data on H. armigera also demonstrated that CN was involved in female sex pheromone biosynthesis (Du et al ., ). Taken together, these results reveal that Ca 2+ /CN is a conserved signal in PBAN‐regulated sex pheromone biosynthesis in both sexes.…”
Section: Discussionmentioning
confidence: 97%